Dorsomorphin attenuates ABCG2-mediated multidrug resistance in colorectal cancer - Li, Xiao-Peng; Cao, Liang-Qi; Yu, Ze-Zhong; He, Ke; Ding, Peng-Bo; Li, Ji-Sheng; Shan, Yi-Yao; Su, Yu-Bin; Yuan, Zhong-Min; Shi, Zhi (Frontiers in Pharmacology, 2024)
Colorectal cancer is a common malignant tumor, and one of the main reasons for its high mortality is chemotherapy resistance. The high expression of ABCG2 in cancer cells and the expulsion of anticancer drugs directly lead to multidrug resistance (MDR). Therefore, the development of new ABCG2 inhibitors to block the active effect of MDR may provide a strategy for the treatment of cancer. In this study, we found that dorsomorphin (also known as compound C or BML-275) potently inhibited the transporter activity of ABCG2, thereby preserving the chemotherapeutic agents mitoxantrone and doxorubicin to antagonize MDR in ABCG2-overexpressing colorectal cancer cells. Additionally, dorsomorphin did not alter ABCG2 protein expression. The results of molecular docking presented that dorsomorphin was bound stably to the ABCG2 binding pocket. These results suggest that dorsomorphin is a potent ABCG2 inhibitor and attenuates ABCG2-mediated MDR in colorectal cancer.